2020
DOI: 10.1111/aas.13592
|View full text |Cite
|
Sign up to set email alerts
|

Causes of late mortality among ICU‐treated patients with sepsis

Abstract: BackgroundPatients with sepsis may have an increased risk of late mortality, but the causes of late death are unclear. This retrospective matched cohort study aimed to determine the causes of late death (≥1 year) among patients with sepsis compared to patients without sepsis.Methods8760 patients with severe sepsis or septic shock (2001 consensus criteria) registered in the Swedish Intensive Care Registry (2008‐2013) were compared with a 1:1 matched (gender, age, SAPS3 probability for death, ICU length of stay)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Patients undergoing major surgeries or remaining in intensive care units suffer high-level LPS and experience a long-term supine position [ 5 , 6 ], which greatly increase the risk of monocyte-endothelial adherence and trigger inflammatory vascular injury. It is detrimental to the patient's recovery, especially for critical patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients undergoing major surgeries or remaining in intensive care units suffer high-level LPS and experience a long-term supine position [ 5 , 6 ], which greatly increase the risk of monocyte-endothelial adherence and trigger inflammatory vascular injury. It is detrimental to the patient's recovery, especially for critical patients.…”
Section: Discussionmentioning
confidence: 99%
“…LPS directly activates monocytes, resulting in its adherence to endothelial cells or the extracellular matrix [4]. The levels of LPS are generally elevated in patients undergoing major surgeries or remaining in the intensive care units [5,6]. In addition, long-term supine position also leads monocyte-endothelial adherence to become easier.…”
Section: Introductionmentioning
confidence: 99%
“…Post‐operative sepsis may have delayed or precluded return to intended oncological treatment, which has been associated with reduced survival 43 . Cancer has been shown to be a major contributor to late deaths after ICU treatment for sepsis 44,45 . The predominance of abdominal infections in the elective surgery patients may also have contributed to mortality, as sepsis of abdominal origin has been associated with higher death rates than other sources of infection 46 …”
Section: Discussionmentioning
confidence: 99%
“…43 Cancer has been shown to be a major contributor to late deaths after ICU treatment for sepsis. 44,45 The predominance of abdominal infections in the elective surgery patients may also have contributed to mortality, as sepsis of abdominal origin has been associated with higher death rates than other sources of infection. 46 We found that patients with sepsis after elective surgery required longer stay in the ICU and the hospital and were more likely to receive invasive mechanical ventilation than other sepsis patients.…”
Section: Pseudomonas Sppmentioning
confidence: 99%
“…At present, there are many known risk factors that increase monocyte-endothelial cell adhesion, including patients undergoing major surgery, intensive care, or long-term bed rest ( Sikorski et al, 2011 ; Ribeiro et al, 2018 ; Schmitt et al, 2020 ; Wilhelms et al, 2020 ; Wu et al, 2020 ). Therefore, the rational use of DEX in critically ill patients should be concerned.…”
Section: Dex's Regulatory Effect On Immune Cells and Inflammationmentioning
confidence: 99%